Dystrophin is required for normal synaptic gain in the Drosophila olfactory circuit - Salinee Jantrapirom (2019)
© 2019 Elsevier B.V. The Drosophila olfactory system provides an excellent model to elucidate the neural circuits that control behaviors elicited by environmental stimuli. Despite significant progress in defining olfactory circuit components and their connectivity, little is known about the mechanisms that transfer the information from the primary antennal olfactory receptor neurons to the higher order brain centers. Here, we show that the Dystrophin Dp186 isoform is required in the olfactory system circuit for olfactory functions. Using two-photon calcium imaging, we found the reduction of calcium influx in olfactory receptor neurons (ORNs) and also the defect of GABA A mediated inhibitory input in the projection neurons (PNs) in Dp186 mutation. Moreover, the Dp186 mutant flies which display a decreased odor avoidance behavior were rescued by Dp186 restoration in the Drosophila olfactory neurons in either the presynaptic ORNs or the postsynaptic PNs. Therefore, these results revealed a role for Dystrophin, Dp 186 isoform in gain control of the olfactory synapse via the modulation of excitatory and inhibitory synaptic inputs to olfactory projection neurons.